STRESS CONDITIONS IN STUDENTS COMPLETING THESIS - Wardi, Rahmanina; Ifdil, Ifdil (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
This study aimed to describe the condition of stress student in completing the thesis viewed from a physiological reaction, psychological, cognitive and behavioral. This study was a descriptive study with a sample of 93 people using simple random sampling. The instrument used in this study is the Student Stress Measurement Scale Completed Thesis (SPSMMS). The study findings revealed that 1) most of the students in completing the thesis stressed in general at a moderate level with a percentage of 35.5%, 2) most of the students in completing the thesis under stress with physiological reactions at a moderate level with a percentage of 40%, 3) most of the students in complete the thesis experiencing psychological stress reactions at a moderate level with a percentage of 38%, 4) most of the students in completing the thesis stressed with cognitive reaction at a moderate level of 35.5%, 5) most students in completing the thesis stressed by the reaction behavior at moderate levels 38.7%. The study recommends necessary counseling services in order to reduce student stress conditions in completing the thesis.